Meta-Analysis: The Effect of Project-Based Learning toward Mathematical Concepts Understanding in Term of Learning Media Utilization - Yestina, Ratna; Ratnaningsih, Nani; Rahayu, Diar Veni; Ni'mah, Khomsatun (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Kerinci, 2024)
Various previous studies on the use of the Project-Based Learning (PjBL) model and its impact on mathematical concepts understanding provide varying reports. This research aims to evaluate the impact of the PjBL model on mathematical concepts understanding and investigate its effects based on the type of instructional media. The research method employed is quantitative with meta-analysis, intended to combine, evaluate, and integrate findings from several published studies. Data was collected through documentary studies by searching articles that published in national and international journals. 32 studies met the predefined inclusion and exclusion criteria. Data analysis was conducted using JASP software version 0.18.1.0. The research results indicate that the effect size of the PjBL model on mathematical concepts understanding is significant in the large category. Moreover, statistically, there is significant differences of effect size of the PjBL model depending on the type of learning media used. The implementation of the PjBL model shows a very large effect size on mathematical concepts understanding when using digital learning media and a large effect when using manual learning media. Meanwhile, without using learning media, the effect size of the PjBL model on mathematical concepts understanding is in the medium category.